Scoping Review: Efek Hesperidin pada Kadar Lipid Tikus Dislipidemia - Rizqia Nurwulandari Putri Setiawan; Arief Budi Yulianti; Sandy Faisal (Bandung Conference Series: Medical Science, 2022)
Abstract. The high incidence of dyslipidemia is one of the risk factors for cardiovascular disease in Indonesia, therefore optimal treatment is needed, but pharmacological therapy has many side effects. Hesperidin herbal treatment with minimal side effects can be considered as complementary therapy. The purpose of this study was to analyze the effect of hesperidin on lipid levels of dyslipidemic rats. This study uses a scoping review method using four databases (Springerlink, Sciencedirect, Pubmed, Proquest) with articles from 2011 – 2021 which with certain keywords obtained 680 articles, then after screening using PICOS four articles were obtained. There are four articles that meet the eligible criteria according to the critical appraisal instrument Arrive 2.0. The research design of the article is entirely true experimental with a population of dyslipidemic rats given hesperidin. The results of all articles showed a decrease in lipid levels (decrease in TC, TG, C-LDL, and increased C-HDL) significantly (p < 0.05). The processes involved in improving the lipid profile in this study were the inhibition of HMG-CoA reductase, ACAT, and regulation of mRNA, C-FABP, and H-FABP that play a role in fat metabolism. Thus, hesperidin can reduce lipid levels in dyslipidemic rats, but this study is qualitative, furthermore it is recommended for further researchers to conduct studies using quantitative methods (meta analysis). Abstrak. Tingginya angka kejadiaan dislipidemia merupakan salah satu faktor risiko dari penyakit kardiovaskular di Indonesia, maka penanganan optimal sangat dibutuhkan, namun terapi farmakologis memiliki banyak efek samping. Pengobatan herbal hesperidin yang minim efek samping dapat dipertimbangkan sebagai terapi komplementer. Tujuan penelitian ini adalah untuk menganalisis efek hesperidin pada kadar lipid tikus dislipidemia. Penelitian ini menggunakan metode scoping review menggunakan empat database (Springerlink, Sciencedirect, Pubmed, Proquest) dengan artikel dari tahun 2011 – 2021 yang dengan kata kunci tertentu didapat 680 artikel, kemudian setelah dilakukan screening menggunakan PICOS didapatkan empat artikel. Artikel yang sesuai kriteria eligible menurut instrumen critical appraisal Arrive 2.0 berjumlah empat artikel. Desain penelitian artikel seluruhnya adalah true experimental dengan populasi tikus dislipidemia yang diberi hesperidin. Hasil dari semua artikel menunjukan penurunan pada kadar lipid (menurunnya K-total, TG, K-LDL, dan meningkatnya K-HDL) secara signifikan (p < 0,05). Proses yang terlibat dalam perbaikan profil lipid pada penelitian ini adalah inhibisi HMG-KoA reduktase, ACAT, dan regulasi mRNA, C-FABP, dan H-FABP yang berperan dalam metabolisme lemak. Maka, hesperidin dapat menurunkan kadar lipid tikus dislipidemia, namun penelitian ini masih bersifat kualitatif dan disarankan untuk peneliti selanjutnya untuk melakukan kajian dengan metode kuantitatif (meta analysis).